The Role Of The Digital Economic Literacy Movement In Supporting MSMEs Sustainability - Dura, Justita; Hamdani, Muhammad Riko (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2024)
Economic growth in Indonesia in the micro, small and medium enterprise (MSMEs) sector often needs help in the short term. Regional government efforts to promote education and literacy have strengthened the importance of digitalization in increasing MSME's income, especially after the pandemic. This research analyses how financial literacy and financial technology (fintech) influence the sustainability of MSMEs in Malang. This type of research is quantitative, using primary data as a questionnaire. The research population consisted of 7920 MSMEs in the city of Malang. The sampling technique used purposive sampling so that 100 MSMEs were obtained as respondents. Data were analyzed using multiple linear regression with the help of SPSS software. The research results show that fintech and financial literacy positively influence the sustainability of MSMEs. Fintech and financial literacy are enough to encourage the expansion and sustainability of MSMEs in Malang. This research can complement existing theories and be a reference for local governments to encourage and facilitate digitalization and financial literacy for MSME players. This research can also be a reference for fintech companies to reach out more to MSMEs and increase fintech socialization.